The effect of palm vitamin E on fetal and newborn development in rats - Hammid, Abdul Niefaizal Abdul; Khaza’ai, Huzwah; Mutalib, Mohd Sokhini Abd; Sanusi, Junedah; Mahdy, Zaleha Abdullah; Mahmood, Maria (Penerbit Universiti Sains Malaysia, 2004)
Palm Vitamin E is an extract of palm oil, which constitutes 25% of tocopherol and 75% of mixed α, δ, γ tocotrienol (Cottrell, 1991). A previous study has found that the feeding of high dosages of palm vitamin E between the range of 250-2500mg/kg body weight (b.w.)did not produce toxicological effects on mice and Sprague Dawley rats (Oo et al., 1992). A study by Rajikin et al. (2001) suggested that a dose of 60mg/kg b.w did not influence the rat gestational period and the number of pups born.